A new approach to classification of Metonymy and figurative images - قهرمان شیری (مطالعات زبانی و بلاغی)
Before producing speech, human beings create an image of the concept of what is to be said in their minds. A host of these conceptions form ideas in our minds but the image and concept are prior to these ideas and it is through reviewing, simile, comparison, analogy, and recurrent associations of the same images that we conceive an idea. Therefore, seeing precedes thinking and thinking that comes with conception and visualization precedes speech. So we have: picture concept thinking speaking. Accordingly the popular saying, âOh Brother youâre the very thinkingâ has something before it, i.e. image and visualization and something after it, i.e. language and speech. If metaphor, simile, allegory, and symbol are related to the domain of image, concept, and visualization, all types of metonymyâexcept for resemblanceâare specifically discussed in the arena of language. This paper seeks to offer a different categorization of metonymy and the author has meant to encompass multiple types of metonymy in this smaller and more manageable category: concomitant metonymy, metonymy of proximity, and metonymy of resemblance.